STRUCTURE, CONDUCT, AND PERFORMANCE OF NUCLEUS ESTATE AND SMALLHOLDER (NES) SCHEME IN OIL PALM SECTOR IN SOUTH KALIMANTAN - Hamdani Hamdani; Nuri Dewi Yanti; Nina Budiwati (TROPICAL WETLAND JOURNAL, 2016)
The purpose of this study was to analyze the structure, conduct, and performance of the nucleus estate and smallholder (NES) scheme in oil palm sector. The results showed that the conduct of partners in partnership generally was in accordance with the functions/tasks, rights and obligations regulated by the local government on the the nucleus estate and smallholder oil palm project. The market structure tended to be not competitive and the partnership system with the nucleus estate and smallholder (NES) scheme did not provide similar profits where the bargaining position of plasma farmers (smallholders) was relatively lower compared with that of the business partners (nucleus estates). Non-competitive market structure did not affect the transaction mechanism of Fresh Fruit Bunches (FFB) products from plasma plantations to necleus estates.